Factors Associated with Readmission Events for BPJS Health Patients in Hospitals - Elasari, Yunina; Wulandari, Rizki Yeni; Nugroho, Tri Adi (GLOBAL HEALTH SCIENCE GROUP, 2024)
The incidence of inpatient readmissions within 30 days is an indicator of the quality management system and service costs in the National Health Insurance (JKN) program. The high incidence of readmissions creates inefficiency and is detrimental not only to BPJS Health as the guarantor, but also to the patients themselves. Readmissions are also a sign of poor quality of health services in hospitals. Summary of JKN data from 2015 to 2019, the hospital readmission rate was 561 per 10,000 cases or 5.61%. This figure is still above the ideal figure, namely above 1%. This study aims to determine the factors associated with the incidence of BPJS Health patient readmissions in hospitals. Quantitative research method with a cross sectional research design on data collected retrospectively. The research sample was taken using a total sampling technique by taking all inpatients at Mutiara Bunda Hospital, Tulang Bawang Regency in 2023, namely 8879 patients. The research data were processed using the person chi-square correlation test. The results of the analysis showed that there was a significant relationship between gender (p < 0.001) and length of stay (p = 0.046) with the incidence of readmissions. There was no relationship between age (p = 0.177) and case severity (p = 0.914) with the incidence of readmission. Hospital management is expected to be able to improve the quality and efficiency of health services through planning the discharge of patients from the moment they are admitted to the hospital, providing education, and continuity of service by prioritizing age at risk to reduce the incidence of readmissions in hospitals.